2007
DOI: 10.1017/s0007114507801553
|View full text |Cite
|
Sign up to set email alerts
|

Reponses of sheep to a vaccination of entodinial or mixed rumen protozoal antigens to reduce rumen protozoal numbers

Abstract: Two rumen protozoa vaccine formulations containing either whole fixed Entodinium or mixed rumen protozoa cells were tested on Merino sheep with the aim of decreasing the number and/or activity of protozoa in the rumen. Negative control (no antigen) and positive control (Tetrahymena corlissi antigens) treatments were also included in the experiment. Blood and saliva were sampled to measure the specific immune response. Protozoal numbers in the rumen were monitored by microscopic counts. Vaccination with protozo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…On a DM basis, it contained 93% organic matter, 9% crude protein, 42% neutral detergent fiber, and 22% acid detergent fiber. Methods used for collection and analysis of feed samples have been described by Williams et al (25). After 4 weeks of acclimatization to the experimental diet, rumen fluid (30 to 50 ml) for construction of 16S rRNA gene libraries was collected from all sheep by insertion of a stomach tube and application of suction 2 to 3 h after they were fed.…”
Section: Methodsmentioning
confidence: 99%
“…On a DM basis, it contained 93% organic matter, 9% crude protein, 42% neutral detergent fiber, and 22% acid detergent fiber. Methods used for collection and analysis of feed samples have been described by Williams et al (25). After 4 weeks of acclimatization to the experimental diet, rumen fluid (30 to 50 ml) for construction of 16S rRNA gene libraries was collected from all sheep by insertion of a stomach tube and application of suction 2 to 3 h after they were fed.…”
Section: Methodsmentioning
confidence: 99%
“…However, the flow out of the rumen protozoa is not proportional to its number in the rumen. Protozoa are retained because of biomass selectively in the rumen (Williams et al, 2008). The removed of rumen protozoa increases the flow of microbial and dietary protein to duodenum.…”
Section: Protozoamentioning
confidence: 99%
“…Methanogens associated with protozoa may shift the fermentation of the latter to produce more hydrogen and hence methane formation, and so the presence of protozoa may increase ruminal methane formation. Williams et al (2008) reported a vaccination trial in sheep using either whole fixed Entodinium or mixed rumen protozoal cells. Administration of these vaccines induced specific antibody responses in blood and saliva, but there was no significant decrease in protozoal numbers following vaccination.…”
Section: Vaccines Targeting Protozoamentioning
confidence: 99%
“…A recent study has shown that antibodies generated against rumen protozoa can remain active for up to 8 h (Williams et al, 2008). However, little is known about the resistance of different classes of antibodies, such as IgG and IgA, to degradation by proteases and peptidases present in the hydrolytic environment of the rumen and how long these antibodies will remain biologically active.…”
Section: Antibody Responses To Antigenic Methanogen Fractions and Selmentioning
confidence: 99%
See 1 more Smart Citation